2015
DOI: 10.4161/15592294.2014.989088
|View full text |Cite
|
Sign up to set email alerts
|

VDR regulation of microRNA differs across prostate cell models suggesting extremely flexible control of transcription

Abstract: The Vitamin D Receptor (VDR) is a member of the nuclear receptor superfamily and is of therapeutic interest in cancer and other settings. Regulation of microRNA (miRNA) by the VDR appears to be important to mediate its actions, for example, to control cell growth. To identify if and to what extent VDR-regulated miRNA patterns change in prostate cancer progression, we undertook miRNA microarray analyses in 7 cell models representing non-malignant and malignant prostate cells (RWPE-1, RWPE-2, HPr1, HPr1AR, LNCaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…For example, miR-106b was amongst the most upregulated miRNA in our analysis and targets several down regulated NRs, including PPARA , suggesting that regulation by miRNAs add yet another layer of complexity within the NR network. Together, these observations of reciprocal NR and miRNA co-expression suggest that epigenetic distortion is important to distort the NR superfamily in the prostate(74, 119121). …”
Section: Introductionmentioning
confidence: 88%
“…For example, miR-106b was amongst the most upregulated miRNA in our analysis and targets several down regulated NRs, including PPARA , suggesting that regulation by miRNAs add yet another layer of complexity within the NR network. Together, these observations of reciprocal NR and miRNA co-expression suggest that epigenetic distortion is important to distort the NR superfamily in the prostate(74, 119121). …”
Section: Introductionmentioning
confidence: 88%
“…It is also noteworthy that datasets have been developed that are aimed at noncoding RNA species. 117,118 Therefore, the diversity of the VDR regulated transcriptome is likely to increase.…”
Section: Identifying Vitamin D Receptor-mediated Transcriptomesmentioning
confidence: 99%
“…The regulation of miRNA expression by 1,25(OH) 2 D 3 is an emerging field of interest and has been shown to be part of the signaling cascades responsible for the effects of 1,25(OH) 2 D 3 on cell proliferation, differentiation, apoptosis, and gene regulation (TABLE 1). Sing et al (414) undertook miRNA microarray profiling in different prostate cell lines ranging from nonmalignant to highly malignant cell types and showed that miRNA expression profiles are highly cell-specific. In addition, they demonstrated in nonmalignant RWPE-1 cells that miRNAs are significantly coregulated with mRNA regulation (414).…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 99%
“…Sing et al (414) undertook miRNA microarray profiling in different prostate cell lines ranging from nonmalignant to highly malignant cell types and showed that miRNA expression profiles are highly cell-specific. In addition, they demonstrated in nonmalignant RWPE-1 cells that miRNAs are significantly coregulated with mRNA regulation (414). Such integration studies will be important to improve miRNA target predictions and to unravel the complex signaling pathways induced by 1,25(OH) 2 D 3 .…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 99%